A rapid screening method for cutinase producing microorganisms - Macedo,Gabriela Alves (2005)
Both cutinase and lipase belong to the esterase group of enzymes (EC 3.1.1.X), which are capable of catalyzing the hydrolysis of ester bonds. Cutinase catalyzes the hydrolysis of cutin, an insoluble biopolyester which is the structural component of plant cuticles. As cutinase is an efficient catalyst in watery or organic media, it is potentially appropriate for the detergent, food and cosmetic industries. The objective of this work was to isolate microorganisms from plants and perform a pre-selection of molds showing esterase producing ability. The selected strains were then submitted to fermentation in media containing cutin. The lipolytic and cutinolytic activities of the supernatant were determined in order to differentiate lipase producers from cutinase-producing strains. The mold strain selected as the best cutinase producer was identified as being Fusarium oxysporium.